2017
DOI: 10.1289/ehp1178
|View full text |Cite|
|
Sign up to set email alerts
|

Urinary BPA and Phthalate Metabolite Concentrations and Plasma Vitamin D Levels in Pregnant Women: A Repeated Measures Analysis

Abstract: Background:In addition to its well-established role in maintaining skeletal health, vitamin D has essential regulatory functions in female reproductive and pregnancy outcomes. Phthalates and bisphenol A (BPA) are endocrine disruptors, and previous research has suggested that these chemical agents may disrupt circulating levels of total 25(OH)D in adults.Objectives:We investigated the relationships between repeated measures of urinary phthalate metabolites and BPA and circulating total 25(OH)D in a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…Johns et al [130] in a cross-sectional study including 4724 adults reported an inverse association between total serum 25(OH)D and both urinary levels of DEHP metabolites in the overall population and urinary BPA in women. The same negative correlation between urinary phthalate metabolites and BPA and circulating total 25(OH)D was demonstrated also in a large prospective cohort of 477 pregnant women [131]. Finally, since PFAS were associated with altered sex steroid [132] and thyroid hormone levels [133] it was hypothesized that they may also affect vitamin D metabolism.…”
Section: Vitamin Dmentioning
confidence: 62%
“…Johns et al [130] in a cross-sectional study including 4724 adults reported an inverse association between total serum 25(OH)D and both urinary levels of DEHP metabolites in the overall population and urinary BPA in women. The same negative correlation between urinary phthalate metabolites and BPA and circulating total 25(OH)D was demonstrated also in a large prospective cohort of 477 pregnant women [131]. Finally, since PFAS were associated with altered sex steroid [132] and thyroid hormone levels [133] it was hypothesized that they may also affect vitamin D metabolism.…”
Section: Vitamin Dmentioning
confidence: 62%
“…To the best of our knowledge, only Cantonwine D et al 46 and Johns LE et al 47 have studied prenatal exposure to BPA. Cantonwine report an average phthalate concentration of 1.95µg/g creatinine and a maximum value of 7.47µg/g creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Four cross-sectional studies examined measures related to bone health: two measured levels of 25-hydroxyvitamin D (25(OH)D, the circulating measure of vitamin D; Johns et al 2016;Johns et al 2017), and two measured bone mineral density (BMD; Min and Min 2014; DeFlorio-Barker and Turyk 2016). All four studies were high quality: the DB percentage scores ranged from 89 to 100% (16 to 18 of a possible 18 points).…”
Section: Bone Healthmentioning
confidence: 99%
“…The studies measured both MEP and MiBP in adults in the United States; three of the four used NHANES data (Min and Min 2014;DeFlorio-Barker and Turyk 2016;Johns et al 2016). Three studies included only women (Min and Min 2014;DeFlorio-Barker and Turyk 2016;Johns et al 2017) and two of the three included only postmenopausal women (DeFlorio-Barker and Turyk 2016; Min and Min 2014).…”
Section: Bone Healthmentioning
confidence: 99%